Analysis of seismic activity on the western part of the Reykjanes Peninsula, SW Iceland, December 2008 - May 2009 - Egill Árni Guðnason 1985- (2014)
In the autumn of 2008 the energy company HS Orka hf. had planned an injection test in the Reykjanes geothermal field in Iceland. This provided an opportunity to study eventual induced seismicity. The Icelandic regional seismic network was not considered sensitive enough to detect and locate small size seismic events. To increase the seismic sensitivity in the area, five temporary seismic stations were installed by the Institute of Earth Sciences at the University of Iceland in December 2008. In addition, data from six SIL stations and three seismic stations operated by the University of Wisconsin were available for the same period. The area under study encompassed mainly the western part of the Reykjanes Peninsula, i.e. the area west of longitude -22.4°, with the addition of the Fagradalsfjall area to the east. The seismic stations of the University of Iceland had to be dismantled in the middle of May 2009, before full-scale injection started. Some small-scale injection was carried out in the Reykjanes geothermal field during the recording period, while more extensive injection was carried out in the Svartsengi geothermal field. Seismic activity from December 2008 to May 2009 was less than on average in the study area. Induced seismicity was not observed in the Reykjanes geothermal field but indications of induced seismicity were observed in the Svartsengi geothermal field. In the Fagradalsfjall area, earthquake activity was mainly confined to one significant earthquake swarm, during the study period, located beneath the southwestern slopes of Fagradalsfjall. Haustið 2008 ákvað HS Orka að hefja niðurdælingaprófanir á jarðhitasvæðinu á Reykjanesi. Því gafst tækifæri til að rannsaka mögulega örvaða smáskjálftavirkni. Til þess að fylgjast með henni setti Jarðvísindastofnun Háskóla Íslands upp fimm skjálftamæla á Reykjanesskaga í desember sama ár, sem voru reknir fram í maí árið 2009. Að auki voru fáanleg gögn frá sex skjálftamælum Veðurstofu Íslands af Reykjanesskaga, í SIL mælakerfinu, ásamt gögnum frá þremur ...